If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 35 = -4d + 7 Reorder the terms: 35 = 7 + -4d Solving 35 = 7 + -4d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '4d' to each side of the equation. 35 + 4d = 7 + -4d + 4d Combine like terms: -4d + 4d = 0 35 + 4d = 7 + 0 35 + 4d = 7 Add '-35' to each side of the equation. 35 + -35 + 4d = 7 + -35 Combine like terms: 35 + -35 = 0 0 + 4d = 7 + -35 4d = 7 + -35 Combine like terms: 7 + -35 = -28 4d = -28 Divide each side by '4'. d = -7 Simplifying d = -7
| (x-0.3)+(2x-0.2)+((40+x)-0.25)=274 | | -10(X+1)=8 | | -6x+15=-33 | | 3x-5(x-4)=-8+3x+3 | | 4x-8=4x+-5 | | 45+4x+7+57x=8 | | 2c-4=c+2 | | 4(3x-2)+4(x+1)=100 | | 7a+2a=18-9 | | 2=-3c+26 | | 3x+8x+4=12x+2 | | 8a+10=82 | | 2x+3-2(x-2)=-3(x+1)+22 | | 8n^2+8n=160 | | 3(X+20)=360 | | 0.92=0.4+0.1 | | 19+(-34)=2.8e+12 | | 8(2x+3)-(11x-4)=3 | | 10(3x-5)=40 | | 2-x=-3(x+4)+6 | | 8(16x+3)-(11x+4)=3 | | 5x-3-2x=12 | | 3(4s+1)=99 | | 2kx+x=2a+b | | 6x-4+3x+1=24 | | b+2b+1= | | 6(2y+5)=3(5y-2) | | 2X-100=22 | | 2(x+3)3(x+1)=24 | | 8(2l+9)=248 | | 5x^2-4x-64.01=0 | | 4x+6x=12x |